2020
DOI: 10.15587/1729-4061.2020.214507
|View full text |Cite
|
Sign up to set email alerts
|

Chemical cellulose-based fibers of decreased flammability

Abstract: The studies reported here have made it possible to determine the optimal ways of fire protection, in which the samples of modified complexite have reduced flammability. The sample with the ions of molybdenum (VI), treated with phosphoric acid, had the highest magnitude of oxygen index among five modified samples of the fiber. This is the most fire-protected sample, which contains three types of flame retardants: nitrogen (amidoxime groups of complexite, phosphorus (treatment with phosphoric acid) and molybdenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Since air is considered a compressible fluid in this context, the equation of D. Bernoulli, used for the flow of an ideal liquid, can be successfully used in the case of any gas flow with minor pressure changes [12]. In particular, with small differences in temperature between the transported air and the environment, it is possible to consider the difference in geometric altitude levels, and the equation of D. Bernoulli can be represented as (13):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since air is considered a compressible fluid in this context, the equation of D. Bernoulli, used for the flow of an ideal liquid, can be successfully used in the case of any gas flow with minor pressure changes [12]. In particular, with small differences in temperature between the transported air and the environment, it is possible to consider the difference in geometric altitude levels, and the equation of D. Bernoulli can be represented as (13):…”
Section: Resultsmentioning
confidence: 99%
“…Experiments conducted in laboratory conditions have shown that the air permeability index for samples before exposure to pressure and moisture is on average, 67.16 cm 3 /cm 2 s (Table 6) [13]. This indicator, after applying pressure and moisture with a mass of 5 kg, decreases to a value of 46.98 cm 3 / cm 2 s; after pressing with a 10 kg press, the device shows 43.74 cm 3 /cm 2 s; after a press load of 15 kg, air permeability decreases to 40.77 cm 3 /cm 2 s; after 20 kg of load, air permeability reduced to 38.01 cm 3 / cm 2 s. It follows that after applying pressure paired with moisture, the air permeability index decreases by 36.95%.…”
Section: Resultsmentioning
confidence: 99%
“…Weighed portions of metal salts were selected in such a way that the number of metal ions in them corresponded to their content in HMCC [23,24]. Simultaneously, for comparison, some studies were carried out in the absence of a catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…There are slight differences in the activity of identical HMCC with CG and NAG complexites. This may be due to the presence in the NAG matrix of a wider range of functional groups involved in the catalytic process, as well as due to the differences in the solvation characteristics of complexites [24]. A significant decrease in the activity of cobalt HMCC (pH 12.2) is probably due to some change in the redox potential of these complexes.…”
Section: The Ability Of Reducing the Concentration Of Hydrogen Sulfid...mentioning
confidence: 99%
“…In addition, the intrinsic characteristics of biodegradability (Vikman et al, 2015), renewability at relatively low cost (Ardanuy et al, 2015), and versatile chemical reactivity (Vuoti et al, 2013) have made desirable cellulose material for many additional potential applications. However, the high hydrophilicity (Rol et al, 2019a) and low thermal resistance (Korovnikova et al, 2020) are limiting factors for certain applications.…”
Section: Introductionmentioning
confidence: 99%